Analysis of Sharia Business Incubation Model Based on Internet of Things (IoT) for Young Entrepreneurs - Luli Iryani; Hendri Hermawan Adinugraha; Ade Gunawan (Universitas Dehasen Bengkulu, 2026)
This research aims to formulate and analyze a sharia business incubation model integrated with Internet of Things (IoT) technology tailored for young entrepreneurs. Amidst rapidly evolving industrial transformations, young Muslim entrepreneurs encounter complex hurdles concerning technological proficiency and compliance with sharia principles. This study utilizes a descriptive qualitative approach intertwined with a comprehensive literature review. Data compilation is derived from academic papers, institutional directives, and empirical documentation published over the preceding five years (2021–2026). The findings demonstrate that a digitalized sharia incubation ecosystem drastically reinforces efficiency, ensures full supply chain transparency (halalan thayyiban), and optimizes real-time monitoring of operations via smart sensors. The integration of Islamic values, such as the prohibition of gharar and maysir, is effectively digitized using automated smart-contract principles within an IoT ecosystem. Conclusively, this structural framework accelerates modern technological literacy while strongly preserving sharia ethics, creating a resilient environment for sustainable and competitive enterprises.